Test the effectiveness of some medications and vitamin D3 used against COVID-19 on Gram-positive and Gram-negative bacteria isolated from people infected with the Coronavirus - Amal F. AL-Gorani; Saadon, Hanan; Ahmed. K. Ajeel; Noor abd alkhudhur salman; Aya Talib jawad; Hussein Adnan Obaid; Hasan Mohsen Koti (University of Thi-Qar Journal of Science, 2024)
The COVID-19 pandemic has led to a search for effective pharmaceuticals and vitamins to combat the virus. These therapies have antiviral capabilities and can affect both gram-negative and gram-positive bacteria. This study aims to assess the effectiveness of various medications and nutrients in treating bacterial infections linked to COVID-19. In vitro, tests will be conducted to evaluate these therapies’ antibacterial efficacy against both gram-negative and gram-positive bacteria. In the current study, we test a group of antibiotics commonly used in treating Coronavirus on different types of Gram-positive and Gram-negative bacteria. They found that Azithromycin was highly effective against both positive and negative bacteria, but its effectiveness decreased when combined with vitamin D. Levofloxacin was the most effective antibiotic, and its efficacy was not affected by the addition of zinc or vitamin D. Acyclovir had a slight effect on bacteria when used alone, but its efficacy improved with zinc. Zinc and Vitamin D had a high degree of effectiveness, but Vitamin D had relatively low efficacy, except against one type of bacteria. The study aims to evaluate the effectiveness of drugs and vitamins against bacterial infections in COVID-19 patients. The results will provide a better understanding of the potential advantages of these medications in controlling bacterial infections. (The abstract should have one paragraph) The study aims to evaluate the effectiveness of drugs and vitamins against bacterial infections in COVID-19 patients. The results will provide a better understanding of the potential advantages of these medications in controlling bacterial infections.